Financial Reporting Quality, Tax Avoidance, Debt Maturity, and Investment Efficiency: The Moderating Role of Corporate Social Responsibility Disclosure - Sukarno, Riandi Satria; Firmansyah, Amrie; Jadi, Pramuji Handra; Fasita, Eta; Febrian, Wahyudi; Sismanyudi, Deddy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This research investigates the influence of financial reporting quality, tax avoidance, and debt maturity on investment efficiency in Indonesia. This study also examines the role of corporate social responsibility disclosure as a moderating variable. Samples of manufacturing companies listed in Indonesia between 2014 and 2019 were selected (414 observations). Using panel regression, this study unveiled a positive effect of financial report quality, while a negative effect of tax avoidance and debt maturity on investment efficiency. Corporate social responsibility disclosure fails to moderate the impact of financial report quality and tax avoidance on investment efficiency. In contrast, corporate social responsibility disclosure strengthens the influence of debt maturity on investment efficiency. This study suggests that the Indonesian Tax Authority needs to improve its supervision on Indonesian companies to suppress tax avoidance by companies that may reduce investment efficiency.